Catalytic properties of Pt-Re/Al2O3 naphtha-reforming catalysts modified by germanium introduced by redox reaction at different pH values - D'ippolito, Silvana Andrea (2009)
Ge was deposited by catalytic reduction on Pt-Re/Al2O 3-Cl base catalysts prepared by coimpregnation. The nominal amounts of Ge incorporated from various impregnation media (H2O, HCl, or NH3) were 0.1, 0.3, 1.0, and 2.0 wt %. The catalysts were characterized by means of the test reactions of cyclohexane dehydrogenation and cyclopentane hydrogenolysis. The catalysts were further characterized by FTIR spectroscopy of adsorbed CO and adsorbed pyridine and by temperature-programmed desorption of pyridine. Blank treatments performed on the Pt-Re/Al 2O3 base catalyst in the different media (without Ge addition) showed that the catalytic reduction method modified the properties of the parent catalyst depending on the pH of the solution. The Brønsted acidity decreased as the impregnation pH was increased, whereas the Lewis acidity of the catalyst was not substantially modified by any of the impregnation media. Catalysts with higher Pt-Re interactions were obtained after treatment in a solution of high pH (NH3 medium). The interaction between Ge and the active metal phase increased with increasing Ge content. This interaction resulted in a decrease of the metal activity in cyclohexane dehydrogenation and cyclopentane hydrogenolysis. Catalyst performances were evaluated in n-heptane (n-C7) reforming under pressure. The n-C 7 tests showed that trimetallic catalysts obtained by impregnation of small quantities of Ge (≤0.3 wt %) using a neutral aqueous solution are the most active and toluene-selective, especially compared to those prepared using HCl or NH3 solution. Nevertheless, the use of ammonia in the impregnation medium allows one to decrease the amount of cracking products. Thus, the catalytic properties might be improved by using a slightly basic medium for the impregnation of Ge.